Modification of Pandan Cutting Machine Based on Anthropometry to Increasing Work Productivity - Wedantara, Pasek Made Sada; Sucipta, I Nyoman; Sanjaya, I Putu Gede Budi (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
This study aimed to improve the efficiency and ergonomics of the pandan cutting machine, which currently causes user complaints such as back, waist, and arm pain. Anthropometric-based modifications were made to the machine’s hopper and engine, using data from 14 adult operators. The modified machine dimensions were: house knife 69.5 × 40 × 6.19 cm, pillow block 10 × 6.3 × 3.9 cm, AS shaft, platen, and cutting knife 38 × 35 × 38 cm, pulley, V-belt, and electric drive 50 × 21 × 20 cm, machine frame 63.5 × 50.4 × 77.5 cm, frame height and silencer rubber 10 × 5 × 35 cm, and body cover 40 × 40 × 62.8 cm. User complaints measured by the Nordic Body Map scored 1.22, categorized as “not sick.” Machine productivity was 0.0014 kg pulse per minute, calculated from average chopping data, working time, and work pulse.